2017
DOI: 10.1002/slct.201700795
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Biological Activities of Gold(I) and Gold(III) Bis(N-Heterocyclic Carbene) Complexes

Abstract: The aim of this research is to evaluate for the first time the in vitro leishmanicidal activity and inhibition of a-glucosidase and b-glucuronidase of new gold(I) and gold(III) complexes involving N-heterocyclic carbene (NHC) ligands, with the general formula [Au(X) n (NHC)R 2 ][BF 4 ] (X=Cl, OAc, R = various aromatic and aliphatic substituents). The Au(III) complexes were shown to have a significant antileishmanial activity, and were also found to be more potent inhibitors of a-glucosidase and b-glucuronidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 82 publications
(74 reference statements)
0
16
0
Order By: Relevance
“…PAF‐R antagonists have exhibited promising results in vitro and in vivo as anti‐angiogenic molecules in several cancer cells and tumors . Gold complexes similar to those tested in this study have already exhibited anti‐inflammatory activity (respiratory burst assay) and cytotoxicity against HeLa (cervical cancer), MCF‐3 (breast cancer), and 3T3 (mouse fibroblast) cell lines . Notably, PAF has been implicated in coordinating angiogenesis, oncogenic transformation, tumor growth, and metastasis in cancer (AA).…”
Section: Figurementioning
confidence: 74%
See 3 more Smart Citations
“…PAF‐R antagonists have exhibited promising results in vitro and in vivo as anti‐angiogenic molecules in several cancer cells and tumors . Gold complexes similar to those tested in this study have already exhibited anti‐inflammatory activity (respiratory burst assay) and cytotoxicity against HeLa (cervical cancer), MCF‐3 (breast cancer), and 3T3 (mouse fibroblast) cell lines . Notably, PAF has been implicated in coordinating angiogenesis, oncogenic transformation, tumor growth, and metastasis in cancer (AA).…”
Section: Figurementioning
confidence: 74%
“…Furthermore, it has been demonstrated that the PAF‐R antagonist PCA4248 has inhibited experimental human melanoma lung metastasis in nude mice . Therefore, as similar gold complexes to those synthesized for this study possess anticancer activity, further research on the antagonistic actions of the herein presented aurates against the PAF‐R is warranted and currently ongoing in our group, as they are potentially powerful anti‐metastatic agents.…”
Section: Figurementioning
confidence: 81%
See 2 more Smart Citations
“…Diabetes is a group metabolic disorder characterized with high blood sugar levels over a long time. Frequent urination, increased thirst, and increased hunger are caused by high blood sugar, which if not addressed to, will result in serious health issues such as diabetic ketoacidosis, hyperosmolar hyperglycemic state, or death, cardiac and vascular diseases, thrombosis, stroke, chronic kidney disease, foot ulcers, and damage to the eyes ,,. Causes of diabetes are either the pancreas fail to produce enough insulin, or the cells of the body fail to respond adequately to the insulin produced.…”
Section: Introductionmentioning
confidence: 99%